Facilitators and barriers to mental health help-seeking in Indian immigrant youth in Gauteng, South Africa - Joji, Timmy; Mapaling, Curwyn (Frontiers in Sociology, 2024)
IntroductionInternational literature has documented significant underutilisation of mental health services among Indian immigrants. This study aimed to identify facilitators and barriers to mental health help-seeking among Indian immigrant youth in South Africa by evaluating their personal and lived experiences.MethodsA qualitative study with a phenomenological design was conducted to understand the lived experiences of Indian immigrant youth regarding mental health help-seeking. Nine participants were recruited through purposive sampling from Gauteng. Data collection was performed through online interviews exploring participants’ lived experiences. Thematic analysis was used to analyse the data.ResultsFive facilitator subthemes were identified: encouragement to seek help for mental health difficulties, social media and mass media influence, university and school environments, availability and awareness of resources, and open conversations about mental health. Four barrier subthemes emerged: individual perspectives on mental health, lack of access to resources, parental factors discouraging help-seeking, and community factors discouraging help-seeking.DiscussionAn improved understanding of these barriers and facilitators may allow other Indian immigrant youth to better manage their help-seeking processes while increasing awareness about similar experiences within the community.